Massive black holes in nuclear star clusters - investigation with SRG/eROSITA X-ray data - Hoyer, Nils; Arcodia, R.; Bonoli, S.; Merloni, A.; Neumayer, Nadine; Zhang, Y.; Comparat, J. (Astronomy and astrophysics, 2024)
Context. Massive black holes (MBHs) are typically hosted in the centres of massive galaxies but they appear to become rarer in lower mass galaxies, where nuclear star clusters (NSCs) frequently appear instead. The transition region, where both an MBH and NSC can co-exist, has been poorly studied to date and only a few dozen galaxies are known to host them. One avenue for detecting new galaxies with both an MBH and NSC is to look for accretion signatures of MBHs. Aims. Here, we use new SRG/eROSITA all-sky survey eRASS:4 data to search for X-ray signatures of accreting MBHs in NSCs, while also investigating their combined occupation fraction. Methods. We collected more than 200 galaxies containing an NSC, spanning multiple orders in terms of galaxy stellar mass and morphological type, within the footprint of the German eROSITA Consortium survey. We determined the expected X-ray contamination from binary stellar systems using the galaxy stellar mass and star formation rate as estimated from far-ultraviolet and mid-infrared emission. Results. We find significant detections for 18 galaxies (~8.3%), including one ultra-luminous X-ray source; however, only three galaxies (NGC 2903, 4212, and 4639) have X-ray luminosities that are higher than the expected value from X-ray binaries, indicative of the presence of an MBH. In addition, the X-ray luminosity of six galaxies (NGC 2903, 3384, 4321, 4365, 4639, and 4701) differs from previous studies and could indicate the presence of a variable active galactic nucleus. For NGC 4701 specifically, we find a variation of X-ray flux within the eRASS:4 data set. Stacking X-ray non-detected galaxies in the dwarf regime M*gal ≤ 109 M⊙) results in luminosity upper limits of a few times 1038 erg s−1. The combined occupation fraction of accreting MBHs and NSCs becomes non-zero for galaxy masses above ~ 107.5 M⊙ and this result is slightly elevated as compared to the literature data. Conclusions. Our data extend, for the first time, towards the dwarf elliptical galaxy regime and identify promising MBH candidates for higher resolution follow-up observations. At most galaxy masses (and with the exception of three cases), the X-ray constraints are consistent with the expected emission from binary systems or an Eddington fraction of at most 0.01%, assuming a black holes mass of 106.5 M⊙. This work confirms the known complexities in similar-type of studies, while providing the appealing alternative of using X-ray survey data of in-depth observations of individual targets with higher resolution instruments.
Online veröffentlicht: 31. Januar 2024
Gesehen am 20.08.2024